Warming and Inhibition of Salinization at the Ocean's Surface by Cyanobacteria. Issue 9 (12th May 2018) - Wurl, O.; Bird, K.; Cunliffe, M.; Landing, W. M.; Miller, U.; Mustaffa, N. I. H.; Ribas‐Ribas, M.; Witte, C.; Zappa, C. J.
Abstract: This paper describes high‐resolution in situ observations of temperature and, for the first time, of salinity in the uppermost skin layer of the ocean, including the influence of large surface blooms of cyanobacteria on those skin properties. In the presence of the blooms, large anomalies of skin temperature and salinity of 0.95°C and −0.49 practical salinity unit were found, but a substantially cooler (−0.22°C) and saltier skin layer (0.19 practical salinity unit) was found in the absence of surface blooms. The results suggest that biologically controlled warming and inhibition of salinization of the ocean's surface occur. Less saline skin layers form during precipitation, but our observations also show that surface blooms of Trichodesmium sp. inhibit evaporation decreasing the salinity at the ocean's surface. This study has important implications in the assessment of precipitation over the ocean using remotely sensed salinity, but also for a better understanding of heat exchange and the hydrologic cycle on a regional scale. Plain Language Summary: We provide high‐resolution in situ observations of large cyanobacterial blooms floating in a biofilm‐like microlayer on the ocean's surface. Our observations show biologically controlled warming and freshening of the surface by the surface blooms that are essential in understanding global heat exchange and the hydrologic cycle. Our study describes a new phenomenon to force "apparent" freshening of the sea surface—in the literature assumed to occur only by precipitation. It further challenges the development of algorithms and validation of remotely sensed temperature and salinity from space. Our finding of active microbial communities in the sea surface microlayer highlights the sea surface as another environment for extreme habitats and microbial adaptation. Our discovery of their influence on satellite observations of sea surface temperature and salinity is fundamental for future research in remote sensing, marine microbiology, air‐sea interaction, and climate regulation. Key Points: Warming and inhibition of salinization of the sea surface are controlled by cyanobacterial surface blooms In the absence of surface blooms, skin layer is generally cooler and saltier A new phenomenon of "apparent" freshening of the sea surface is described, which has been assumed to occur only by precipitation